1998
DOI: 10.1002/prs.680170407
|View full text |Cite
|
Sign up to set email alerts
|

The effects of valve wheel size, operation position and in‐line pressures on required torque for gate valves

Abstract: Some of the hazards encountered by process plant operators involve the operation of in-line valves to control, start, and to stopflow. Torque required to operate valves may vary according to valve wheel size, in-line pressure, and valve flange position (open/closed). This study determined how valve wheel size, in-line pressure and valve position (open/closed) affect torque required to actuate a valve. Data were gathered with each combination of size, pressure and position for 336 valves in an operating petroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…However, anecdotal reports from workers reveal that the torque required to open valves (CCW) is much greater than closing them. These reports are corroborated by data from Parks and Schulze (1998) in a study of the required closing and opening torque of industrial valves. They found that the torque to open a valve (CCW) was much greater than the torque required to close a valve (CW) (means of 149 N⋅m vs. 109 N⋅m, respectively).…”
Section: Torque Directionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, anecdotal reports from workers reveal that the torque required to open valves (CCW) is much greater than closing them. These reports are corroborated by data from Parks and Schulze (1998) in a study of the required closing and opening torque of industrial valves. They found that the torque to open a valve (CCW) was much greater than the torque required to close a valve (CW) (means of 149 N⋅m vs. 109 N⋅m, respectively).…”
Section: Torque Directionsupporting
confidence: 87%
“…Field studies have shown that the required tangential force to "crack" open a hand wheel valve of 40.6 cm (16 in.) diameter at a petroleum refinery averaged 788 N (160 N⋅m; Parks & Schulze, 1998). Although the 788-N force as measured in the field study is lower than the level approved by MSSVFI (1,000 N), many workers are not able to exert almost 800 N of shear force on a hand wheel without the use of a hand wheel extension arm.…”
Section: Literature Reviewmentioning
confidence: 98%
See 3 more Smart Citations